Recombinant factor VIIa analog (vatreptacog alfa [activated]) for treatment of joint bleeds in hemophilia patients with inhibitors: A randomized controlled trial - Erich V. de Paula (2018)
Summary. Background:A recombinant factor VIIa analog (NN1731; vatreptacog alfa [activated]) was developed to provide safe, rapid and sustained resolution of bleeds in patients with hemophilia and inhibitors. Patients/Methods:This global, prospective, randomized, double-blinded, active-controlled, dose-escalation trial evaluated and compared one to three doses of vatreptacog alfa at 5, 10, 20, 40, and 80μgkg -1 with one to three doses of recombinant FVIIa (rFVIIa) at 90μgkg -1 in the treatment of acute joint bleeds in hemophilia patients with inhibitors. The primary endpoint comprised adverse events; secondary endpoints were evaluations of immunogenicity, pharmacokinetics, and efficacy. Results and Conclusions:Overall, 96 joint bleeds in 51 patients ( > 12 years of age) were dosed. Vatreptacog alfa was well tolerated, with a low frequency of adverse events. No immunogenic or thrombotic events related to vatreptacog alfa were reported. A high efficacy rate of vatreptacog alfa in controlling acute joint bleeds was observed; 98% of bleeds were controlled within 9h of the initial dose in a combined evaluation of 20-80μgkg -1 vatreptacog alfa. The efficacy rate observed for rFVIIa (90%) is consistent with data from published clinical trials. The trial was not powered to compare efficacy, and further trials are needed to investigate the efficacy of vatreptacog alfa as compared with that of rFVIIa. The trial was registered at ClinicalTrials.gov (Registration Number: NCT00486278). © 2011 International Society on Thrombosis and Haemostasis.